Alternative fuels for marine applications: Biomethanol-biodiesel-diesel blends. (15th July 2019) - Paulauskiene, Tatjana; Bucas, Martynas; Laukinaite, Airida
Abstract: Recent emission related limits imposed on marine fuel are causing the ship owners to look for alternative fuels to comply with the new limits. Depletion of fossil fuel raised the attention of researchers to investigate renewable energy sources such as biodiesel and alcohol. Methanol blends as marine fuel leads to drastically reducing sulfur and particle emissions, adopting methanol also shows lower nitrogen oxide emissions and, when produced from renewable sources, lower CO2 emissions over the entire fuel lifecycle. Biodiesel has the potential in fulfilling the environment and economic concerns as it is a renewable and sustainable energy source. Empirical relationships among physical-chemical properties and blends of biomethanol-biodiesel-diesel were assessed by direct gradient analysis. It was inspected how the physical-chemical properties change along an ordination axis of detrended correspondence analysis using "vegan" package in R. Physical-chemical properties from the multivariate model were predicted by using two types of blends' data. The first one was based on the simulated ranges from the used data in calibration of the redundancy analysis, whereas the second one consisted of simulated ranges extrapolated up to 99% of both blends. It was concluded that a blend with 10% biomethanol and 20% biodiesel was the most suitable alternative fuel for marine applications (considering to ISO 8217:2012 standard and environmental requirements for marine fuel).